How to identify oceanic crust—Evidence for a complex break-up in the Mozambique Channel, off East Africa - Klimke, Jennifer; Franke, Dieter; Gaedicke, Christoph; Schreckenberger, Bernd; Schnabel, Michael; Stollhofen, Harald; Rose, Jens; Chaheire, Mohamed (Tectonophysics, 2016)
The identification of oceanic crust at riftedmargins plays a crucial role in academic research understanding rifting mechanisms and the architecture of continent–ocean boundaries, and is also important for hydrocarbon exploration extending into deeperwater. In this paper,we provide aworkflow for the determination of the crustal nature in the Mozambique Channel, east of Davie Ridge, by presenting a compilation of several geophysical attributes of oceanic crust at divergent margins. Previous reconstructions locate the Davie Ridge at the trace of a transform fault, along which Madagascar drifted to the south during the breakup of Gondwana. This implies a sharp transition from continental to oceanic crust seaward of Davie Ridge. Using newmultichannel seismic profiles offshore northernMozambique, we are able to identify distinct portions of stretched basement east of Davie Ridge. Two phases of deformation affecting the basement are observed, with the initial phase resulting in the formation of rotated fault blocks bounded by listric faults. Half-grabens are filled with wedge-shaped, syn-extensional sediments overlain by a prominent unconformity that northward merges with the top of highly reflective, mildly deformed basement, interpreted as oceanic crust. The second phase of deformation is associated with wrench faulting and probably correlates with the southward drift of Madagascar,which implies that the preceding phase affected basement generated ormodified prior to the opening of the West Somali Basin. We conclude that the basement is unlikely to consist of normal oceanic crust and suggest that the first extensional phase corresponds to rifting betweenMadagascar and Africa.We find evidence for a wide area affected by strike–slip deformation, in contrast to the earlier proposed major single transform fault in the vicinity of Davie Ridge and suggest that the Mozambique Channel area to the north of Madagascar may be classified as an oblique rather than sheared margin.
Keywords: Davie Ridge; Mozambique Channel; Oblique margin; Oceanic crust; Reflection seismic data; Rifting